Melatonin level as a risk factor for age-related macular degeneration - N. S. Khodzhaev (Scientific Сentre for Family Health and Human Reproduction Problems, 2021)
Background. The current trend towards an increase in age-related macular degeneration (AMD) incidence rate in the population, including the working-age population, with a possible loss of professional activity, indicates the need for early preclinical identification of risk groups, timely prevention and treatment. In the prevention and treatment of AMD, the prospect of using melatonin is being actively discussed.Aim: to analyze serum and tear fluid levels of melatonin in patients with AMD and study their correlation with risk factors.Materials and methods. In the course of the study, two groups were formed: the main group - patients with non-exudative AMD and senile cataract (n = 40) and the reference group - conditionally healthy patients without AMD and cataract (n = 20). Patients of both groups were surveyed to identify risk factors for AMD. The content of melatonin in blood serum and lacrimal fluid was determined by enzyme-linked immunosorbent assay using the Melatonin ELISA Kit (USA).Results. In the course of the study, it was found that the concentration of melatonin in blood serum and tear fluid in patients with AMD was significantly lower than in patients of the reference group (p <0.05). Serum and tear fluid melatonin levels depend on the following factors: age, body mass index (BMI), arterial hypertension, eye color, insomnia, and night work. It is possible that the local determination of melatonin in the lacrimal fluid can be a biomarker in the determination of ophthalmic pathological conditions.Conclusion. The obtained results can be used as recommendations for clarifying individual regimens for the use of melatonin, especially in the treatment of patients with AMD.